2017
DOI: 10.5114/wiitm.2017.72322
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous radiofrequency and microwave ablation in the treatment of renal tumors - 10 years of experience.

Abstract: IntroductionThe standard radical treatment of renal cell carcinoma is surgical resection, but it is not suitable for patients with serious medical comorbidities and solitary kidney tumors. Minimally invasive ablation techniques could be an appropriate therapeutic alternative.AimTo retrospectively evaluate the technical success, mid-term and long-term efficacy and safety of radiofrequency and microwave ablation in patients with small renal tumors.Material and methodsOver the course of 10 years, 91 ablation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…RCC size also affects the success rate of LA treatment. It has been reported that 26.5% of patients need to undergo two or more LA operations to achieve successful treatment, especially for large RCC; for tumors >4.5 cm, approximately 7.4% of patients undergo LA treatment 44 . Mauri et al 45 reported that among 149 patients treated with thermal ablations with a median follow‐up of 54 months, 18.1% received multiple successful ablations due to incomplete ablation, local tumor progression, distant tumor progression, or multiple tumor foci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RCC size also affects the success rate of LA treatment. It has been reported that 26.5% of patients need to undergo two or more LA operations to achieve successful treatment, especially for large RCC; for tumors >4.5 cm, approximately 7.4% of patients undergo LA treatment 44 . Mauri et al 45 reported that among 149 patients treated with thermal ablations with a median follow‐up of 54 months, 18.1% received multiple successful ablations due to incomplete ablation, local tumor progression, distant tumor progression, or multiple tumor foci.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 26.5% of patients need to undergo two or more LA operations to achieve successful treatment, especially for large RCC; for tumors >4.5 cm, approximately 7.4% of patients undergo LA treatment. 44 Mauri et al 45 reported that among 149 patients treated with thermal ablations with a median follow-up of 54 months, 18.1% received multiple successful ablations due to incomplete ablation, local tumor progression, distant tumor progression, or multiple tumor foci. Simultaneous use of ultrasound and computed tomography in ablation surgery can improve the ability to immediately detect RCC tissue that has not been sufficiently ablated, thereby guiding immediate secondary ablation.…”
Section: Pvaluementioning
confidence: 99%
“…There is an extensive evidence in the literatures from metaanalysis, cohort studies, and case series on the technical outcomes, the safety and the effectiveness of the use of MWA for the treatment of T1a RCCs [15,27,[42][43][44][45][46][47][48][49][50][51][52][53] (Table 2). All the literatures reported the MWA of RCC under US or CT guidance.…”
Section: Effectivenessmentioning
confidence: 99%
“…Image-guided local ablation therapy was introduced as a radical treatment, which was useful to improve overall survival (OS) of patients [7][8][9]. Radiofrequency ablation (RFA) and microwave ablation (MWA) are two most often performed ablative treatments.…”
Section: Introductionmentioning
confidence: 99%